1996
DOI: 10.1007/bf03172721
|View full text |Cite
|
Sign up to set email alerts
|

Two measures of the quality of group care for infants and toddlers

Abstract: Two sets of quality measures of group care were used to assess their predictive power for two sets of measures of the development of infant and toddlers in group day care. One of the quality measures we investigated was the Early Childhood Environment Rating Scale (ECERS). We replicated the findings of Scarr, Eisenberg, & DealerDeckard (1994) which were that the total score of the ECERS represents a global index and that the 37 items making up the scale are redundant and could be shortened considerably withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 13 publications
0
12
0
3
Order By: Relevance
“…Our results further indicate that it would not be sufficient to randomly select a set of items from the scale as suggested by Scarr et al (1994) or Beller et al (1996) regarding the ECERS, or Perlman et al (2004) on the ECERS-R. The randomly chosen sets of 12 examined in the current study had alphas ranging from .59 to .68, much lower than the .89-.92 range reported by Scarr et al (1994), and much lower than our two factors individually (.81 and .87) or combined (.88).…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Our results further indicate that it would not be sufficient to randomly select a set of items from the scale as suggested by Scarr et al (1994) or Beller et al (1996) regarding the ECERS, or Perlman et al (2004) on the ECERS-R. The randomly chosen sets of 12 examined in the current study had alphas ranging from .59 to .68, much lower than the .89-.92 range reported by Scarr et al (1994), and much lower than our two factors individually (.81 and .87) or combined (.88).…”
Section: Discussionmentioning
confidence: 77%
“…They further reported that the 37-item scale was reducible to a randomly selected set of 12 items that was as reliable at predicting quality as the overall scale (Scarr et al, 1994). This finding was later replicated by Beller et al (1996) and Perlman et al (2004).…”
Section: Previous Factor Analytic and Scale Reduction Techniques For mentioning
confidence: 92%
See 2 more Smart Citations
“…Toutefois, une telle qualité s'avère difficile à atteindre et, surtout, à maintenir dans les services de garde. En effet, plusieurs recherches menées aux États-Unis et ailleurs dans le monde rapportent que le niveau de qualité s'avère généralement médiocre ou faible (Beller, Stahnke, Butz, Stahl et Wessels, 1996 ;Bigras, Bouchard, Cantin, Brunson, Coutu, Lemay, Tremblay, Japel et Charron, 2010 ;Burchinal, Roberts, Riggins, Zeisel, Neebe et Bryant, 2000 ;Petrogiannis et Melhuish, 1996). Diverses hypothèses ont été évoquées pour expliquer ce faible niveau de qualité, comme le sous-financement des services, mais aussi le niveau de formation exigé pour le personnel éducateur.…”
Section: Initiatives Visant à Préparer Les Enfants à L'écoleunclassified